AB0310 Prevalence of Secondary Sarcopenia in Mexican Rheumatoid Arthritis Patients Measured with New Ewsop Criteria. (10th June 2014) - Lozada Perez, C.A.; Espinosa Morales, R.; Miranda, T.S.; Valerio Morales, I.A.; Gonzalez, A.S.; Hernandez Rivera, A.; Santiago Cordova, J.L.; Martinez Juarez, G.; Hernandez Gonzalez, L.
Abstract : Background: Background:Rheumatoid arthritis (RA) cause sarcopenia (SCP). The European Working Group on Sarcopenia in Older People (EWGSOP) 1, 2 defined primary and secondary SCP cut-off values. Studies have reported prevalence (PV) of SCP in RA whit the previous criteria, it was between 21.4% and 33.3%. The SCP is considered a disability cause in patients with RA Objectives: Objective: To estimate prevalence of secondary SCP in patients with RA using new EWGSOP criteria; associate joint function, quality of life and physical activity with the presence of SCP. Methods: Methods: An observational, cross-sectional study. Inclusion criteria: Patients with RA that fulfilling ACR criteria/EULAR 2010, 18-59 years. Exclusion Criteria: Patients with previous arthroplasty, unstable chronic illness, stroke with motor deficits. Demographics, clinimetric (DAS28, CDAI, HAQ-DI and EuroQol) were collected. The measurement of body composition was performed by multifrequency bioimpedance (InBody 720®), physical performance (walking speed), muscle strength (Handgrip strength). Descriptive and inferential statistical analysis was used according to the variable type and distribution using Stata12®. Results: Results: 46 patients were studied, 86.9% female, mean age 44.9±10.6 years; family history of RA in 45.6%; duration of RA 9.9±6.8 years, time of diagnosis of RA 7.8±6.5 years, comorbidities found: diabetes 4.8%, hypertension 10.8%, history of non prosthetic orthopedic surgery 17.4% and 19.6% previous fracture. We found a DAS28 3.64 (1.74-6.38), CDAI 7.5 (0-32). Anthropometric measures: weight 67±10.2 kg, height 1.56±0.007 m, BMI 27.4±3.6, body fat mass 25.7±8.3 kg (reference population 11.4-18.2 kg), percent body fat 37.9±8.5 (reference 18-28%), waist hip ratio 0.96±0.07 (reference 0.75-0.85), muscle mass (MM) in women median 8.88 (6.8-10.4) kg/m 2 (reference >6.76kg/m 2 ), men MM median 10.2 (6.7-12.5) kg/m 2 (reference >10.76 kg/m 2 ), handgrip strength in women of 14.9 kg (2.6-27 kg) (reference >20 kg) in men and 25.7 kg (18-38) (reference >30 kg), walking speed 0.96±0.23 m/s (reference >1 m/s). We found prevalence of 6.5% pre-SCP, SCP 2.1% and did not find patient with severe SCP. Comparing the quality of life, joint function between groups with and without SCP, we found no statistically significant differences. Conclusions: Conclusions: We found less PV of SCP with respect to previously published, although our population probably does not represent all patients with RA. Our population had more overweight and percent body fat. We found no difference between these groups in quality of life, joint function and activity. Applying new EWGSOP criteria we obtain accurate data for diagnosed secondary SCP in RA patients. References: Cruz-Jentoft AJ, Baeyens JP, Bauer JM, et al. Sarcopenia: European consensus on definition and diagnosis: report of the European Working Group on Sarcopenia in Older People. Age Ageing 2010;39(4):412–23. Janssen I, Baumgartner R, Ross R et al. Skeletal muscle cutpoints associated with elevated physical disability risk in older men and women. Am J Epidemiol 2004; 159: 413–21. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5502